Composite metal lithium negative electrode plate, preparation method thereof and lithium battery
By using composite metal lithium anode sheets in lithium-ion batteries, a blended solution of metal lithium, aromatic compounds and ether solvents and a blended slurry of conductive materials, binders and lithium-philic compounds is used to form a uniform negative electrode material, which solves the problems of limited energy density of the negative electrode material of traditional lithium-ion batteries and short cycle life and low safety of metal lithium materials, and achieves higher energy density and more stable cycle performance.
Patent Information
- Application Number
- CN202311120358.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The specific capacity of the negative electrode material of traditional lithium-ion batteries is limited, resulting in the upper limit of the energy density of lithium-ion batteries. At the same time, metal lithium, as the negative electrode material, has problems such as short cycle life, low safety and incompatible with liquid electrolytes.
Using a composite metal lithium negative electrode sheet, a metal lithium solution is formed by mixing metal lithium, aromatic compounds and ether solvents, and mixing them with conductive materials, binders and lithium-philic compounds to form a blended slurry, and coating them on the negative electrode current collector. This method uses lithium-philic compounds as the nucleation site of lithium element to form a uniform negative electrode material to inhibit the growth of lithium dendrites.
The migration rate and electrochemical reaction rate of lithium ions are improved, the uniformity of lithium deposition is enhanced, the growth of lithium dendrites is inhibited, and the circulation stability and safety of metal lithium batteries are improved.
Smart Images

Figure CN119542353A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a composite metal lithium negative electrode sheet and a preparation method thereof, and a lithium battery. Background Art
[0002] Lithium-ion batteries are a type of efficient and environmentally friendly chemical power source that are widely used in mobile communications, electric vehicles, energy storage and other fields.
[0003] Lithium-ion batteries are composed of four parts: positive electrode, negative electrode, electrolyte and separator. The negative electrode is an important component of the battery and affects the battery's performance such as energy density, life and safety. The traditional negative electrode material of lithium-ion batteries is mainly graphite, but the specific capacity of graphite is only 372mAh / g, which seriously limits the upper limit of the energy density of lithium-ion batteries. Relatively speaking, the gram capacity of metallic lithium is 3860mAh / g, which is more than 10 times that of graphite, and has the lowest electrode potential, so that metallic lithium can be used as the negative electrode of the battery, forming a large potential difference with the positive electrode, thereby generating a higher voltage, so it has an absolute advantage in improving the battery energy density. However, metallic lithium currently faces the following problems as a negative electrode: (1) short cycle life; (2) low safety; (3) incompatibility with liquid electrolyte.
[0004] Domestic and foreign studies have shown that through the functional design and optimization of energy materials, it is expected to achieve dendrite-free growth of metallic lithium, inhibit volume deformation, and improve the utilization efficiency of metallic lithium. Nat. Commun. 6, 8058 (2015, Angew. Chem. Int. Ed. 56 (2017) reported that the negative electrode prepared by using carrier materials, reducing local current density, and regulating lithium deposition methods to inhibit the growth of metallic lithium dendrites, improve the safety and cycle efficiency of lithium metal negative electrodes. However, the current methods for preparing composite lithium negative electrodes using carrier materials mainly include hot melting methods and electrochemical deposition methods. Among them, the hot melting method requires modification or modification of the surface of the carrier material, which limits the selection range of the carrier material, and the high temperature operating conditions also increase the safety risks of the preparation process; while the electrochemical deposition method is to assemble the carrier material and metallic lithium into a battery, apply current to deposit lithium on the surface of the carrier material, and prepare a composite lithium negative electrode. This process is complex, inefficient, costly, and difficult to prepare and apply on a large scale.
[0005] Prior art CN1690694A discloses a solution of forming a liquid negative electrode with metallic lithium and biphenyl or condensed-ring aromatic compounds, benzene-ring-containing organic compounds, and ether compounds, which can alleviate the problem of interface contact. However, the flowing liquid as the negative electrode requires special devices or battery cell designs to maintain a certain shape, making the battery system complicated and increasing the cost, and cannot be widely used. Summary of the invention
[0006] The purpose of the present invention is to provide a composite metal lithium negative electrode sheet and a preparation method thereof and a lithium battery. The composite metal lithium negative electrode sheet provided by the present invention has the characteristics of high electronic conductivity, ionic conductivity and high uniformity, enhances the migration rate of lithium ions, improves the uniformity of lithium deposition, inhibits the growth of lithium dendrites, and improves the cycle stability of metal lithium batteries.
[0007] To this end, in a first aspect, an embodiment of the present invention provides a composite metal lithium negative electrode sheet comprising: a negative electrode current collector and a composite metal lithium negative electrode material;
[0008] The composite metal lithium negative electrode material is obtained by drying a mixed slurry of a metal lithium solution, a conductive material, a binder, and a lithium-philic compound; the mixed slurry is coated on the negative electrode current collector;
[0009] In the composite metal lithium negative electrode sheet, the lithium-philic compound is used as a nucleation site for lithium elements, and the lithium-philic compound is combined with a metal lithium solution to produce a synergistic effect to form a uniform negative electrode material, so that lithium ions are uniformly embedded and de-embedded during the charge and discharge process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metal lithium negative electrode material.
[0010] Preferably, the metallic lithium solution is a mixed solution of metallic lithium, aromatic compounds and ether organic solvents; the metallic lithium includes: a combination of one or more of metallic lithium strips, metallic lithium powders and metallic lithium sheets; the aromatic compounds include: a combination of one or more of biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives; the ether solvent includes: a combination of any one or more of ethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, ethylene oxide and propylene oxide;
[0011] The conductive material includes: any one or more combinations of multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive graphite, and conductive carbon black;
[0012] The binder includes: polytetrafluoroethylene;
[0013] The lithium-philic compounds include copper oxide (CuO), nano zinc oxide (ZnO), nano niobium oxide (Nb 2 O 5 ), lithium niobate (LiNbO 3 ), any one or more combinations of zinc-based metal organic frameworks (Zn-MOFs).
[0014] Preferably, the negative electrode current collector is copper foil.
[0015] Preferably, the mass ratio of metallic lithium to aromatic compound in the metallic lithium solution is 3:7-5:5.
[0016] Preferably, in the blended slurry, the mass ratio of the metallic lithium solution is 93% to 96%, the mass ratio of the conductive material is 1.5% to 2.5%, the mass ratio of the binder is 1.5% to 2.5%, and the mass ratio of the lithium-philic compound is 1% to 2%.
[0017] In a second aspect, an embodiment of the present invention provides a method for preparing the composite metal lithium negative electrode sheet described in the first aspect, the preparation method comprising:
[0018] Dissolving metallic lithium and an aromatic compound in an ether organic solvent according to a mass ratio under an inert environment to obtain a metallic lithium solution;
[0019] Adding a conductive material, a binder and a lithium-philic compound to the metallic lithium solution, and dispersing at high speed to obtain a blended slurry;
[0020] The mixed slurry is coated on the negative electrode current collector in an inert environment, and then rolled to obtain the composite metal lithium negative electrode sheet after drying.
[0021] Preferably, the mass ratio of the metallic lithium to the aromatic compound is 3:7-5:5;
[0022] In the blended slurry, the weight ratio of the metallic lithium solution is 93% to 96%, the weight ratio of the conductive material is 1.5% to 2.5%, the weight ratio of the binder is 1.5% to 2.5%, and the weight ratio of the lithium-philic compound is 1% to 2%;
[0023] The viscosity of the blended slurry is 1500-3500 mPa·s, and the solid content is 45%-50%;
[0024] The negative electrode current collector is copper foil with a thickness of 6 to 12 μm;
[0025] The coating surface density of the blended slurry on the negative electrode current collector is 88 to 108 g / m 2 , coating thickness is 130~150μm;
[0026] The drying temperature is 85-110°C, and the drying time is 0.5-2h;
[0027] The inert environment is a nitrogen environment or an argon environment.
[0028] Preferably, the orbital speed of the high-speed dispersion is 10 rpm-20 rpm, the rotational speed is 600 rpm-1500 rpm, and the dispersion time is 5-20 min.
[0029] Preferably, the method further comprises: adding an aromatic compound to the blended slurry to adjust the viscosity of the blended slurry.
[0030] In a third aspect, an embodiment of the present invention provides a lithium battery, comprising: a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is the composite metal lithium negative electrode sheet described in the first aspect.
[0031] The composite metal lithium negative electrode sheet provided by the embodiment of the present invention is prepared by forming a metal lithium solution with metal lithium, an aromatic compound and an ether solvent, and then mixing it with a conductive agent, a binder and a lithium-philic compound to form a negative electrode blend slurry containing a lithium composite, and coating it on a negative electrode current collector. The composite metal lithium negative electrode of the present invention has higher energy density and capacity, and can meet the growing demand. The composite metal lithium negative electrode sheet has good electronic conductivity and ion conductivity characteristics, and can improve the diffusion migration rate and electrochemical reaction rate of lithium ions. At the same time, in the present invention, the lithium-philic compound is used as a lithium element nucleation site, and the lithium-philic compound is combined with the metal lithium solution to produce a synergistic effect to form a uniform negative electrode material, so that lithium ions are uniformly embedded and de-embedded during the charge and discharge process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metal lithium negative electrode material, improving the cycle life of the battery, and reducing the safety risk of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of a composite metal lithium negative electrode sheet provided in an embodiment of the present invention;
[0033] Figure 2 A flow chart of a method for preparing a composite metal lithium negative electrode sheet provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0035] The embodiment of the present invention provides a composite metal lithium negative electrode sheet, such as Figure 1 As shown, the composite metal lithium negative electrode sheet includes: a negative electrode current collector and a composite metal lithium negative electrode material;
[0036] The composite metal lithium negative electrode material is obtained by drying a mixed slurry of a metal lithium solution, a conductive material, a binder, and a lithium-philic compound; the mixed slurry is coated on a negative electrode current collector; in the mixed slurry, the mass proportion of the metal lithium solution is 93% to 96%, for example, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%; the mass proportion of the conductive material is 1.5% to 2.5%, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.2%. 1%, 2.2%, 2.3%, 2.4%, 2.5%; the mass proportion of the binder is 1.5% to 2.5%, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%; the mass proportion of the lithium-philic compound is 1% to 2%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%.
[0037] In the composite metal lithium negative electrode sheet, the lithium-philic compound has a high affinity. The lithium-philic compound serves as a nucleation site for lithium elements, and can also balance the distribution of lithium ions, making them evenly dispersed in the negative electrode, reducing the phenomenon of local excess lithium, and facilitating uniform deposition. The combination of the lithium-philic compound and the metal lithium solution produces a synergistic effect to form a uniform negative electrode material, so that lithium ions are evenly embedded and de-embedded during the charge and discharge process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metal lithium negative electrode material.
[0038] The metallic lithium solution is a mixed solution of metallic lithium, aromatic compounds and ether organic solvents; the mass ratio of metallic lithium to aromatic compounds in the metallic lithium solution is 3:7-5:5, that is, the mass ratio of metallic lithium material is 30% to 50%, for example, 30%, 35%, 40%, 45%, 50%; the mass ratio of aromatic compounds is 50%-70%, for example, 50%, 55%, 60%, 65%, 70%.
[0039] Metallic lithium includes: a combination of one or more of metallic lithium strips, metallic lithium powder, and metallic lithium sheets; aromatic compounds include: a combination of one or more of biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene, or anthracene derivatives; ether solvents include: a combination of any one or more of ethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, ethylene oxide, and propylene oxide.
[0040] The conductive material includes: any one or more combinations of multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive graphite, and conductive carbon black.
[0041] Binders include: polytetrafluoroethylene.
[0042] Lithium-philic compounds include copper oxide (CuO), nano zinc oxide (ZnO), nano niobium oxide (Nb 2 O 5 ), lithium niobate (LiNbO 3 ), any one or more combinations of zinc-based metal organic frameworks (Zn-MOFs).
[0043] The negative electrode current collector is copper foil, and the thickness is preferably 6 to 12 μm.
[0044] The composite metal lithium negative electrode sheet of the present invention can be prepared by Figure 2 The preparation method is prepared by the following main steps:
[0045] Step 110, dissolving metallic lithium and an aromatic compound in an ether organic solvent according to a mass ratio under an inert environment to obtain a metallic lithium solution;
[0046] The mass ratio of metallic lithium to aromatic compounds is 3:7-5:5; the mass ratio of metallic lithium material is 30% to 50%, for example, 30%, 35%, 40%, 45%, 50%; the mass ratio of aromatic compounds is 50%-70%, for example, 50%, 55%, 60%, 65%, 70%.
[0047] The inert environment is a nitrogen environment or an argon environment.
[0048] Step 120, adding a conductive material, a binder and a lithium-philic compound to the metallic lithium solution, and dispersing at high speed to obtain a blended slurry;
[0049] In the blended slurry, the mass proportion of the metallic lithium solution is 93% to 96%, for example, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%; the mass proportion of the conductive material is 1.5% to 2.5%, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%; the mass proportion of the binder is The mass proportion is 1.5% to 2.5%, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, and 2.5%; the mass proportion of the lithium-philic compound is 1% to 2%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, and 2%.
[0050] The viscosity of the blended slurry is 1500-3500 mPa·s, and the solid content is 45%-50%. The viscosity of the blended slurry can be adjusted by adding aromatic compounds to the blended slurry.
[0051] The orbital speed of high-speed dispersion is 10rpm-20rpm, the rotation speed is 600rpm-1500rpm, and the dispersion time is 5-20min.
[0052] Step 130, coating the blended slurry on the negative electrode current collector under an inert environment, and rolling it after drying to obtain a composite metal lithium negative electrode sheet;
[0053] The negative electrode current collector is copper foil with a thickness of 6 to 12 μm; for example, 6 μm, 8 μm, 10 μm, 12 μm; and a coating surface density of 88 to 108 g / m 2 , for example 88g / m 2 , 90g / m 2 , 92g / m 2 , 94g / m 2 , 96g / m 2 , 98g / m 2 , 100g / m 2 , 102g / m 2 , 104g / m 2 , 106g / m 2 , 108g / m 2 ; The coating thickness is 130-150μm, for example, 130μm, 134μm, 138μm, 142μm, 146μm, 150μm; The drying temperature is 85-110℃, for example, 85℃, 88℃, 90℃, 94℃, 98℃, 102℃, 106℃, 110℃.
[0054] The inert environment is a nitrogen environment or an argon environment.
[0055] The drying time is 0.5 to 2 hours, for example, 0.5 hours, 0.8 hours, 1.1 hours, 1.4 hours, 1.7 hours, and 2 hours.
[0056] The composite metal lithium negative electrode sheet of the present invention can be applied to lithium batteries.
[0057] The composite metal lithium negative electrode sheet provided by the embodiment of the present invention is prepared by mixing a lithium-containing solution formed by metal lithium-aromatic compounds and ether solvents with carbon nanotubes and a binder to form a lithium-containing composite negative electrode slurry, and then coating it on a negative electrode current collector. Compared with traditional graphite materials, composite metal lithium negative electrodes have higher energy density and capacity, and can meet the growing demand. The composite metal lithium negative electrode sheet has good electronic conductivity and ion conductivity characteristics, can improve the diffusion migration rate and electrochemical reaction rate of lithium ions, and at the same time, the uniform combination of the lithium-philic compound and liquid metal lithium used in the present invention can induce uniform deposition of lithium ions, inhibit the formation of lithium dendrites, improve the cycle life of the battery, and reduce the safety risks of lithium metal batteries.
[0058] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0059] The present invention is further described in detail below through the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, not intended to limit the protection scope of the present invention.
[0060] Example 1
[0061] Step 1: Place 5 g of lithium metal sheets in a stirring kettle in a glove box, add 10 g of ethylene glycol dimethyl ether and 1 g of biphenyl, and stir for 10 min at a revolution of 10 r / min and a rotation of 500 r / min to form a lithium metal solution.
[0062] Step 2, add 0.2g multi-walled carbon nanotubes, 0.2g polytetrafluoroethylene, and 0.11g lithium niobate to the metallic lithium solution, increase the rotation speed to 16r / min, 1000r / min, and stir for 20min to fully mix, and finally add a small amount of ethylene glycol dimethyl ether and continue stirring for 5min to adjust the viscosity to obtain a negative electrode slurry with a viscosity of 3100mp·s and a solid content of 45.6% to form a metallic lithium negative electrode blended slurry.
[0063] Step 3: Coat the metal lithium negative electrode slurry on 8 μm copper foil with a coating surface density of 99 g / m 2 The coating thickness is 130 μm, and it is dried in an oven at 88°C for 2 hours and rolled to form a composite metal lithium negative electrode sheet.
[0064] Example 2
[0065] Step 1: Place 10 g of lithium metal in a stirring kettle in a glove box, add 50 g of ethylene oxide and 10 g of naphthalene, and stir for 15 min at a revolution of 10 r / min and a rotation of 600 r / min to form a lithium metal solution.
[0066] Step 2, add 3.2g of nano-graphite, 3.4g of polytetrafluoroethylene and 2.6g of nano-zinc oxide to the metallic lithium solution, increase the speed to 16r / min of revolution and 1200r / min of rotation, stir for 15min to fully mix, and finally add a small amount of ethylene oxide and continue stirring for 5min to adjust the viscosity to obtain a negative electrode slurry with a viscosity of 3400mp·s and a solid content of 47.5.% to form a metallic lithium negative electrode blended slurry.
[0067] Step 3: Coat the lithium metal negative electrode slurry on a 6 μm copper foil with a coating surface density of 102 g / m 2 The coating thickness is 142 μm, and it is dried in an oven at 88°C for 1.5 h and rolled to form a composite metal lithium negative electrode sheet.
[0068] Example 3
[0069] Step 1: Place 6 g of metallic lithium powder in a stirring kettle in a glove box, add 20 g of tetrahydrofuran and 14 g of biphenyl, and stir for 8 min at a revolution speed of 12 r / min and a rotation speed of 700 r / min to form a metallic lithium solution.
[0070] Step 2, add 0.2g of conductive carbon black, 0.4g of polytetrafluoroethylene and 0.3g of zinc-based metal organic framework to the metallic lithium solution, increase the rotation speed to 15r / min of revolution and 1500r / min of rotation, stir for 5min to fully mix, and finally add a small amount of tetrahydrofuran and continue stirring for 5min to adjust the viscosity to obtain a negative electrode slurry with a viscosity of 3300mp·s and a solid content of 47% to form a metallic lithium negative electrode blended slurry.
[0071] Step 3: Coat the metal lithium negative electrode slurry on a 7 μm copper foil with a coating surface density of 101 g / m 2 The coating thickness is 142 μm, and it is dried in an oven at 92°C for 1 hour and rolled to form a composite metal lithium negative electrode sheet.
[0072] Comparative Example 1
[0073] This comparative example provides a lithium metal negative electrode, which includes a current collector and a lithium metal layer with the same thickness as that of the metal lithium negative electrode slurry dried and rolled in Example 1. The current collector is a copper foil with a thickness of 20 μm, and the lithium metal layer is obtained on the surface of the current collector by electrochemical deposition.
[0074] The composite metal lithium negative electrode of the above embodiment and the lithium metal negative electrode of the comparative example are respectively assembled with the positive electrode sheet, the separator and the electrolyte into a soft-pack lithium battery, and the cycle performance is tested. Among them, the positive electrode sheet is a positive electrode sheet obtained by mixing a lithium manganate positive electrode, a conductive carbon black SP and polyvinylidene fluoride (PVDF) with a mass ratio of 97:1.5:1.5, and then coating the slurry on an aluminum foil and baking and rolling it. The electrolyte is 1M LiPF6@ethylene carbonate + diethyl carbonate (EC+DEC). The cycle performance test conditions are 25°C, 1C charge and discharge cycle.
[0075] The test results are shown in Table 1:
[0076]
[0077]
[0078] Table 1
[0079] It can be seen from the above table:
[0080] Compared with Comparative Example 1, the 100-week capacity retention rate of Examples 1-3 has obvious advantages. This is because the negative electrode slurry formed by forming a lithium-containing solution with metallic lithium-aromatic compounds and ether solvents and then mixing them with conductive materials, binders and lithium-philic compounds to form a lithium-containing composite has good uniformity. The lithium-philic compounds are used as nucleation sites for lithium elements, and the combination of the lithium-philic compounds and the metallic lithium solution produces a synergistic effect to form a uniform negative electrode material, so that lithium ions are uniformly embedded and de-embedded during the charge and discharge process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metallic lithium negative electrode material and improving the cycle stability of the battery.
[0081] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A composite metal lithium negative electrode sheet, characterized in that: The composite metal lithium negative electrode sheet comprises: a negative electrode current collector and a composite metal lithium negative electrode material; The composite metal lithium negative electrode material is obtained by drying a mixed slurry of a metal lithium solution, a conductive material, a binder, and a lithium-philic compound; the mixed slurry is coated on the negative electrode current collector; In the composite metal lithium negative electrode sheet, the lithium-philic compound is used as a nucleation site for lithium elements, and the lithium-philic compound is combined with a metal lithium solution to produce a synergistic effect to form a uniform negative electrode material, so that lithium ions are uniformly embedded and de-embedded during the charge and discharge process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metal lithium negative electrode material.
2. The composite metal lithium negative electrode sheet according to claim 1, characterized in that: The metal lithium solution is a mixed solution of metal lithium, aromatic compounds and ether organic solvents; the metal lithium includes: a combination of one or more of metal lithium strips, metal lithium powders and metal lithium sheets; the aromatic compound includes: a combination of one or more of biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives; the ether solvent includes: a combination of any one or more of ethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, ethylene oxide and propylene oxide; The conductive material includes: any one or more combinations of multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive graphite, and conductive carbon black; The binder includes: polytetrafluoroethylene; The lithium-philic compound includes any one or more combinations of copper oxide (CuO), nano zinc oxide (ZnO), nano niobium oxide (Nb2O5), lithium niobate (LiNbO3), and zinc-based metal organic frameworks (Zn-MOFs).
3. The composite metal lithium negative electrode sheet according to claim 1, characterized in that: The negative electrode current collector is copper foil.
4. The composite metal lithium negative electrode sheet according to claim 1, characterized in that: The mass ratio of metallic lithium to aromatic compound in the metallic lithium solution is 3:7-5:
5.
5. The composite metal lithium negative electrode sheet according to claim 1, characterized in that: In the blended slurry, the metal lithium solution accounts for 93% to 96% by mass, the conductive material accounts for 1.5% to 2.5% by mass, the binder accounts for 1.5% to 2.5% by mass, and the lithium-philic compound accounts for 1% to 2% by mass.
6. A method for preparing the composite metal lithium negative electrode sheet according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Dissolving metallic lithium and an aromatic compound in an ether organic solvent according to a mass ratio under an inert environment to obtain a metallic lithium solution; Adding a conductive material, a binder and a lithium-philic compound to the metallic lithium solution, and dispersing at high speed to obtain a blended slurry; The mixed slurry is coated on the negative electrode current collector in an inert environment, and then rolled to obtain the composite metal lithium negative electrode sheet after drying.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the metallic lithium to the aromatic compound is 3:7-5:5; In the blended slurry, the weight ratio of the metallic lithium solution is 93% to 96%, the weight ratio of the conductive material is 1.5% to 2.5%, the weight ratio of the binder is 1.5% to 2.5%, and the weight ratio of the lithium-philic compound is 1% to 2%; The viscosity of the blended slurry is 1500-3500 mPa·s, and the solid content is 45%-50%; The negative electrode current collector is copper foil with a thickness of 6 to 12 μm; The coating surface density of the blended slurry on the negative electrode current collector is 88 to 108 g / m 2 , coating thickness is 130~150μm; The drying temperature is 85-110°C, and the drying time is 0.5-2h; The inert environment is a nitrogen environment or an argon environment.
8. The preparation method according to claim 6, characterized in that: The high-speed dispersion has an orbital speed of 10-20 rpm, an autorotational speed of 600-1500 rpm, and a dispersion time of 5-20 min.
9. The preparation method according to claim 6, characterized in that: The method further includes: adding an aromatic compound into the blended slurry to adjust the viscosity of the blended slurry.
10. A lithium battery comprising: A positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is a composite metal lithium negative electrode sheet as described in any one of claims 1 to 5.
Citation Information
Patent Citations
Reagent for lithiation reaction, preparation method and use thereof
CN1690694A
Cited By
Metal-lithium composite belt and preparation method thereof
CN120033212A
Lithium metal negative electrode loaded with lithium-loving phase, preparation method of lithium metal negative electrode and lithium metal battery
CN121260746A